Investigating the influence of ambient light spectrum on the thickness and band gap of halide-perovskite for indoor photovoltaic application - Borah, Chandra Kamal; Goyary, Sagar Sing; Borah, Lakhi Nath; Ţălu, Ştefan; Kumar, Sanjeev (Solar energy, 2023)
[Display omitted] •A perovskite PV cell has been modeled as FTO/ZnO/MAPbI3-xClx/Spiro-MeOTAD.•The cell has been studied under AM1.5 solar spectra, LED, CFL, and INC light condition.•SCAPS-1D software has been used to study the performance.•Initially, the η has been found to be 23.3%, 40.08%, 39.22%, and 29.15% respectively under AM 1.5, LED, CFL, and INC light.•The effect of these ambient lights on the thickness and bap gap of MAPbI3-xClx has also been carried out.•The η has been achieved at 41.95%, 41.13%, and 32.82% efficiency accordingly.•This investigation paves the way for the practical implementation of such indoor PV cells for IoT applications. Mixed halide perovskite photovoltaic (PV) cells show remarkable efficiency under outdoor sunlight conditions, but they also have a lot of potential for use in the indoor light environment. Unfortunately, the theoretical, as well as experimental studies on the application of mixed halide perovskite photovoltaic cells for indoor light harvesting, are still lagging. Here, a perovskite PV cell has been modelled as FTO/ZnO/MAPbI3-xClx/Spiro-MeOTAD and studied its performance under AM1.5G solar spectra, Light Emitting Diode (LED) light, Compact Fluorescent Light (CFL), and Incandescent (INC) light condition by using SCAPS-1D (Version 3.3.10), solar cell simulation software. Initially, the power conversion efficiency (η) is 23.3 %, 40.08 %, 39.22 %, and 29.15 % respectively under AM 1.5, LED, CFL, and INC light. Further, the effect of the ambient lights i.e. LED, CFL and INC on the thickness and bap gap (Eg) of MAPbI3-xClx has also been carried out and achieved 41.95 %, 41.13 %, and 32.82 % efficiency accordingly. This investigation into the thickness and band gap effect of MAPbI3-xClx for indoor performance paves the way for the practical implementation of such indoor PV cells for modern Internet of Things (IoT) applications.